Assessments for neuromuscular control after an anterior cruciate ligament injury to decide upon return to sports - Blasimann, A.; Koenig, I.; Baert, I.; Baur, H.; Vissers, D. (British Journal of Sports Medicine, 2021)
Background Adequate neuromuscular control of the knee could be one element to prevent secondary injuries after an anterior cruciate ligament (ACL) injury. However, it is unclear which measurements should be used to assess neuromuscular control of the knee for a safe return to sports (RTS).